Association Beetween Nutrient Intake and Dietary Diversity with Obesity Status in College Students - Reni Novia; Fitri Ardiani; Fitri Handayani; Zulhaida Lubis; Etti Sudaryati (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Obesity is a nutritional problem that has become one of the most pressing global public health challenges of the 21st century. According to the SKI 2023 results, the prevalence of obesity among individuals aged 18 and older in Sumatera Utara was 24.3%. Several factors influencing are broadly related to issues of nutritional intake and dietary diversity. Objective: To analyze relationship between nutrient intake and dietary diversity with incidence obesity among undergraduate students in Public Health program at the Universitas Sumatera Utara 2023/2024. Methods: This study used cross-sectional design with 245 participants. Data collected included food recall, BMI, WHR, and IDDS score calculations. The relationship was analyzed using Chi-Square test. Results and discussion: Most subjects had normal nutritional status, but prevalence of obesity 21.6% and risk of central obesity 14.7% were still found. The adequacy levels of energy, fat, and carbohydrates were predominantly in the severe deficiency category, while protein adequacy tended toward the normal category, and nearly all subjects fiber deficiency. Most students had moderate dietary diversity. The analysis results showed no significant association between adequacy levels of energy, protein, carbohydrates, fiber, and dietary diversity with the prevalence of obesity or risk of central obesity. However, there was significant association between fat intake levels and risk of central obesity. Conclusion: It’s important to control fat intake and improve dietary quality by increasing fiber consumption and dietary diversity, along with controlling other factors not examined in this study (physical activity, sleep quality, stress, genetic factors, and eating habits).